Western blotting guru - Najafov, Ayaz; Hoxhaj, Gerta (Elsevier/Academic Press, an imprint of Elsevier, 2017)
Western Blotting Guru provides researchers in molecular biology with a handy reference for approaching and solving challenging problems associated with immunoblotting setup and optimization. As a laboratory guide, it emphasizes the technical aspects of efficiently employing immunoblotting as a tool in molecular biology laboratories. The book covers the basic science underlying immunoblotting and detailed description of the method parameters, followed by good benchtop practices, tips and tricks for obtaining high-quality data and a detailed troubleshooting guide addressing a variety of problem types.--Provided by publisher.